PENGARUH VARIABEL ROLE CONFLICT, ROLE AMBIGUITY DAN JOB INSECURITY TERHADAP KEPUASAN KERJA AKUNTAN PENDIDIK Studi Empiris pada Lingkungan Perguruan Tinggi di Pulau Jawa - Purwanto, Marini; Nasir, M. (JURNAL BISNIS STRATEGI, 2001)
This study intents to examine the effect of role conflict, role ambiguity, job insecurity on the job satisfaction of educators accountants, and examine that result of this research consistent with before research by Ashford et al. (1989). Pasewark Strawser (1996). and Suwandi & Indriantoro (1999). The purpose of this research is find empirically evidence about level job satisfaction of educators accountants. This study is hopes to give contribution to the development university on the increase performance of educators accountants.The data were collected by distributing quetionaires only 181 paper were retarned completely and analyzed by using SPSS version 10. Sample selection method using purposive sample and snowballing. Hypotheses are tested using multiple regression model.The results indicated that role conflict, role ambiguity, job insecurity have positive effect and significant on job satisfaction, so hypotheses in in this study rejected. On the environment work of educators accountants not influential on reduction job satisfaction. The results study not consistent with previously research by Ashford et al. (1989), Pasewark, Strawser (1996), and Suwandi & Indriantoro (1999). Research in the future hopes can examine another wariable may be can influence job satisfaction of educators accountants.